Treatment of petroleum refinery wastewater using extended aeration activated sludge - Gasim, H. (Trans Tech Publications Ltd, 2015)
The petroleum refinery wastewater biological treatment is widely investigated because of the potential complete mineralization and environmental aspect. In this study, petroleum refinery wastewater was treated in an extended aeration activated sludge (EAAS) reactor A, operated in parallel with EAAS reactor B as a control, fed with municipal wastewater. The chemical oxygen demand (COD) organic loading rate (OLR) of the refinery wastewater in reactor B was approximately 0.057 kg COD/m3d compared to reactor A of 0.004 kg COD/m3d throughout the study period. The flowrate for both reactors was maintained at 21.4 L/day. Food to microorganism (F/M) ratio, COD, mixed liquor suspended solids (MLSS), and mixed liquor volatile suspended solids (MLVSS) were monitored throughout the study period. The result indicated high removal efficiency of organic matter of approximately 87 as COD with 2582 mg/L of the petroleum refinery wastewater as influent and 140 mg/L as effluent. Copyright Â© 2015 Trans Tech Publications, Switzerland.